Research on the Evaluation Model of Investment Benefits of Major Power Transmission and Transformation Projects Based on BWM and TOPSIS Methods - Tian Xin (E3S Web of Conferences, 2020)
Transmission and transformation project is the foundation of power grid construction, the development of large-scale transmission projects can not only realize the optimal allocation of resources, but also improve the overall efficiency of power transmission. This paper takes the investment benefit of major power transmission and transformation project as the research object, and explores its complete evaluation system in depth. According to the characteristics of various types of projects, an evaluation indicator system has been built to meet all kinds of major power transmission and transformation projects. Considering the differences in the focus of evaluation indicators of different projects, the paper puts forward an indicator evaluation idea based on BWM method (Best-Worst Method) and TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution Method), so as to establish an investment benefit evaluation model applicable to various power transmission and transformation projects. Finally, the paper verifies the above investment benefit evaluation model through the actual engineering project, and the evaluation process and results show the practicality and superiority of the model.